Evoluzione della Cerchia Legnosa in Quercus Suber L. - Ciampi, Clara (Giornale botanico italiano, 1951)
Summary The evolution of the wood ring in Quercus Suber L. (from October 1946 to September 1947). ? The Author has studied the wood ring evolution in Quercus Suber L. during one year, by means of sampling monthly the main stem and young branches of a specimen growing as S. Giust near Florence (m. ca. 500 ov. s. l.). In Quercus Suber L. cambial activity starts off probably first in the stem and secondly in the branch; it comes to an end sooner in the latter and in a clear cut manner, ending later in the stem and in a dragged out manner. There are two separate stages in wood ring development: cell walls undergo a thickening process during the first one, and lignification during the second one. This last stage is drawn out for a long time ending, both in stem and branch, only shortly before the cambium becomes active again in the following' spring. Cambial activity in the branch begins before the buds open. Wood growth cycle in Quercus Suber is in perfect harmony with prevailing climatic conditions. The cambial tissue starts dividing at the end of March, during a period of remarkable rainfall and of increase of temperature, continues its activity in May and June, ending completely in Summer, when temperature and dryness reach their highest values.
doi: 10.1080/11263505109431516